Some results of research of the Ostolopovo settlement in the Alekseyevsky district of the Republic of Tatarstan - Rudenko Konstantin A. (Поволжская археология, 2012)
The article is devoted to the study of Ostolopovo unfortified settlement site (Alekseyevsky district, Tatarstan). It dates back to the 11th — first half of the 12th century. Expensive imported products, items made of precious metals, and weapons and armor fragments have been found on the site. The population lived in wooden houses with stoves of identical design. No traces of occupation in agriculture and handicrafts have been discovered on the settlement site. The collection of ceramics, articles made of iron, non-ferrous metals, and wood, found on the settlement site, is of great interest for the study of antiquities referring to Volga Bulgaria in the first half of the pre-Mongol period.